Diamondoid-structured polymolybdate-based metal–organic frameworks as high-capacity anodes for lithium-ion batteries. Issue 37 (26th April 2017) - Wang, Yuan-Yuan; Zhang, Mi; Li, Shun-Li; Zhang, Shu-Ran; Xie, Wei; Qin, Jun-Sheng; Su, Zhong-Min; Lan, Ya-Qian
Abstract : Two novel isostructural polyoxometalate (POM)-based coordination polymers were obtained. The results reveal thatNENU-507 could be directly utilized as an anode material for lithium-ion batteries with outstanding performance. Abstract : Two novel isostructural polyoxometalate (POM)-based metal–organic frameworks (MOFs) with diamond topology, NENU-506 andNENU-507, were hydrothermally synthesized. They not only combine the advantages of both POMs and MOFs, but also show excellent chemical and thermal stability. Notably, NENU-507 exhibited a high reversible capacity of 640 mA h g −1 after 100 cycles when applied as an anode material in lithium-ion batteries.